2016
DOI: 10.1097/bpo.0000000000000498
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Retrograde Drilling in Juvenile Osteochondritis Dissecans of the Talus

Abstract: Level IV-therapeutic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 22 publications
0
44
0
1
Order By: Relevance
“…Comparative literature for the talus is lacking. In a case series of six patients, Mosquijo et al observed a relief of symptoms in all patients, but only three patients (50%) showed complete healing on radiographs on a mean follow-up of 37 months [31].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Comparative literature for the talus is lacking. In a case series of six patients, Mosquijo et al observed a relief of symptoms in all patients, but only three patients (50%) showed complete healing on radiographs on a mean follow-up of 37 months [31].…”
Section: Discussionmentioning
confidence: 95%
“…Frail bone structure after repetitive attempts to reach the OCD lesion can result in iatrogenic fractures [29,30]. Precise retrograde drilling without damaging the articular cartilage surface is thus very important [18,31]. It is not always possible to use mechanical targeting devices, similar to those used for tunnel positioning in anterior cruciate ligament reconstruction [18], because their pre-shaped design does not always allow for accurate placement [10,17].…”
Section: Discussionmentioning
confidence: 99%
“…In our institution, regardless of lesion size, RD is performed for OLTs in skeletally immature children when the talar articular cartilage is intact, because skeletally immature children have a good ability for induction of subchondral bone revascularization and stimulation of new bone formation. 2,7,10 Masquijo et al 8 reported that arthroscopic RD was effective for symptom relief in skeletally immature children, although 50% of cases had persistent lesions on radiographs. In the present study, primary OLT treatment with RD resulted in a good Berndt and Harty clinical outcome in 7 ankles (87.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Masquijo et al 8 showed that arthroscopic RD can be effective for symptom relief in skeletally immature children. However, no studies have evaluated the preoperative and postoperative computed tomography (CT) findings of RD in skeletally immature children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation